AB1089 Diagnosis of Systemic Inflammatory Diseases in Patients with Fever Referred to A Quick Diagnosis Unit: Experience of A Third Level Teaching Hospital in Barcelona. (10th June 2014) - Brito Zeron, P.; Nicolás Ocejo, D.; Jordán, A.; Retamozo, S.; Lόpez-Soto, A.; Bosch, X.
Abstract : Background: Quick diagnosis units (QDUs) are an effective, useful and cost-saving model for the diagnosis of a wide range of diseases. Fever is a common symptom for multiple diseases and is becoming an increasing cause for referral to QDUs. Currently, studies have not evaluated the efficacy and usefulness of QDUs for the diagnosis of inflammatory diseases that present with fever. Objectives: To analyze the prevalence of inflammatory diseases in patients who are referred to the QDU for fever. To analyse the factors related to the efficacy and usefulness of diagnosis of inflammatory diseases in a QDU. Methods: Prospective evaluation of 186 patients referred to the QDU between November 2008 and April 2011 due to undiagnosed fever (>38°C for at least 1 week). Exclusion criteria included patients in whom fever was resolved before the first visit at the QDU, patients without complete medical records and patients who were lost to follow-up. Results: A total of 176 QDU patients were evaluated, 53% women and 47% men (mean age of 44, 70±16, 34). The main etiology of fever were infectious diseases (71%), followed by inflammatory diseases (13%), miscellaneous (7%), fever without diagnosis (7%) and neoplasia (2%). The main etiologies of inflammatory diseases were (1) systemic autoimmune diseases in 11 patients: undifferentiated autoimmune diseases in 6, Sjögren syndrome in 3, SLE in 1 and microscopic polyangiitis in 1; (2) rheumatological diseases in 6 patients: polymyalgia rheumatica in 3, rheumatoid arthritis, reactive arthritis and undifferentiated inflammatory oligoarthritis in 1, respectively; (3) organ-specific autoimmune diseases in 3: autoimmune hyperthyroidism, autoimmune hypothyroidism, primary biliary cirrhosis; (4) autoinflammatory syndromes (Mediterranean periodic fever) in 2 patients; (5) fibro-inflammatory diseases (IgG4-related disease) in 1 patient. When we compared patients with inflammatory diseases with respect to other etiologies of fever, patients with inflammatory diseases had a higher mean age (51.48±16.45 vs 43.69±16.13, p=0.033), required a higher mean number of QDU visits (3.52±1.76 vs 2.54±1.11, p<0.001) and days (39.17±31.9 vs 23.82, p=0.008) to reach a final diagnosis, required a higher mean number of blood analysis (1.70±0.88 vs 1.22±0.61, p=0.001) and other complementary tests (X-rays, CT-scans). The inflammatory disease that took the longest to diagnose (151 days and 10 QDU visits in total) was IgG4-related disease. After reaching a final diagnosis of fever, patients with inflammatory diseases were more frequently referred to specialized departments (65% vs 14%, p<0.001) in comparison to other etiologies of fever mostly referred to primary care centers. Conclusions: Inflammatory diseases were the second most common cause of fever in the QDU, with undifferentiated autoimmune diseases the most common, followed by Sjögren syndrome and polymyalgia rheumatica. Diagnosis of inflammatory diseases was a challenge, requiring more complementary tests and more number of visits and days to reach a diagnosis compared with other fever etiologies. IgG4-related disease was the most challenging as a cause of fever of unknown origin. QDU is an alternative model for diagnosis of inflammatory diseases that present with fever. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5089